Recyclable glass fiber reinforced nylon / ABS (Acrylonitrile Butadiene Styrene) alloy composite material as well as preparation method and application thereof

By adding glass fiber, nylon resin, ABS resin and other components to nylon material, a recycling-recyclable glass fiber reinforced nylon/ABS alloy composite material is prepared, which solves the problems of complex spraying process and difficulty in processing recycling materials, and achieves efficient spraying and Improved material performance.

CN119410135APending Publication Date: 2025-02-11HENAN TIANHAI HEJU NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411688598.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

When spraying auto parts, the surface painting process of nylon materials is complicated and the recycling material is difficult to handle, which is prone to problems of paint falling off and material deformation.

Method used

The fiberglass reinforced nylon/ABS alloy composite material is used to improve the strength and compatibility of the material and simplify the paint spraying process by adding glass fiber, nylon resin, ABS resin, compatibility agent, toughening agent and other components.

Benefits of technology

It realizes efficient spraying of nylon materials, improves the adhesion of paint and the strength of materials, simplifies the paint spraying process, meets the production needs of automobile owners, and promotes the secondary utilization of recycled materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410135A_ABST
    Figure CN119410135A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer material processing, and discloses a recyclable glass fiber reinforced nylon / ABS alloy composite material as well as a preparation method and application thereof. The recyclable glass fiber reinforced nylon / ABS alloy composite material is prepared from the following components in percentage by weight: 25 to 35 percent of low-carbon nylon material, 5 to 15 percent of nylon resin, 6 to 17 percent of glass fiber, 25 to 30 percent of ABS resin, 0.2 to 0.8 percent of main antioxidant, 0.2 to 0.8 percent of auxiliary antioxidant, 1 to 5 percent of compatilizer 1, 1 to 10 percent of compatilizer 2, 5 to 13.5 percent of flexibilizer and 1.5 to 3 percent of nylon black masterbatch. The compatilizer 1 comprises 64-74% of nylon 6 resin, 24-34% of ABS (Acrylonitrile Butadiene Styrene) resin and 1-2% of a lubricant. According to the composite material prepared according to the formula and the method, secondary utilization of recycled materials is achieved, the strength and rigidity of the recycled materials are improved, the influence on the environment is reduced, the adhesiveness of paint on the surfaces of the materials can be improved, the complexity of the paint spraying procedure is simplified, and the production requirements of automobile main engine plants are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material processing, in particular to a nylon / ABS alloy composite material. Background Art

[0002] In the process of entering modernization, green and low-carbonization must also be achieved. Therefore, current automobile OEMs not only put forward the demand for recyclable and recyclable materials, but also have high requirements for material strength and quality. Spraying of plastic parts is a complex process in the process of vehicle manufacturing. Most materials need to undergo complex pretreatment before spraying. The treatment steps are solvent cleaning or chemical degreasing, electrostatic dust removal and flame treatment. Among them, flame treatment is a key process in pretreatment. The main purpose of flame treatment is to use a strong oxidizing flame to oxidize the plastic surface, increase the surface tension of the plastic substrate, make the paint and the substrate surface better combined, and improve the adhesion of the paint. If this process is not handled well, it will lead to insufficient surface tension of the material, so that the paint cannot infiltrate the surface of the material, causing the paint to fall off during spraying. Recycled materials are more difficult to handle due to the uncertainties of their use and recycling. In addition, there are usually a large amount of solvents in the paint, and its curing process is heating curing. After the above process, the recycled materials usually appear deformed, corroded, and the performance is reduced. Publication number CN105504654A discloses a PA / ABS alloy material, but when spraying paint on its surface, on the one hand, the pretreatment before spraying is relatively complicated and requires flame treatment, which may cause uneven surface tension, resulting in partial paint falling off of the sprayed parts. On the other hand, after facing the harsh environmental influences during the spraying process, the material may deform and its performance may deteriorate.

[0003] Therefore, how to provide an easy-to-spray, green, low-carbon, recyclable glass fiber reinforced nylon / ABS alloy composite material is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention

[0004] In order to solve the technical problems of complex painting process of nylon material surface, coping with the adverse environmental impact during the spraying process and further realizing the reuse of nylon waste, the present invention proposes a recyclable glass fiber reinforced nylon / ABS alloy composite material and its preparation method and application.

[0005] To achieve the above object, the technical solution of the present invention is implemented as follows:

[0006] A recyclable glass fiber reinforced nylon / ABS alloy composite material, which comprises, by weight, 25%-35% of low-carbon nylon material, 5%-15% of nylon resin, 6%-17% of glass fiber, 25%-30% of ABS resin, 0.2%-0.8% of primary antioxidant, 0.2%-0.8% of secondary antioxidant, 1%-5% of compatibilizer I, 1%-10% of compatibilizer II, 5%-13.5% of toughening agent and 1.5%-3% of nylon black masterbatch;

[0007] The compatibilizer I comprises 64%-74% of nylon 6 resin, 24%-34% of ABS resin and 1%-2% of lubricant.

[0008] The low-carbon nylon material is at least one of nylon 6 parts crushed material, nylon 6 head material, nylon 6 nozzle crushed material, nylon 6 black spot material, nylon 6 discolored material and nylon 6 mixed color material generated in the automobile production process.

[0009] The above nylon resin is nylon 6 resin with an intrinsic viscosity of 2.45-2.8 dL / g; the ABS resin is prepared by suspension polymerization and has a rubber content of 20-35%.

[0010] The glass fiber is short glass fiber that has been surface treated with a coupling agent.

[0011] The main antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], and the auxiliary antioxidant is tris[2,4-di-tert-butylphenyl]phosphite.

[0012] The compatibilizer II is ABS grafted with maleic anhydride or maleimide.

[0013] The toughening agent is maleic anhydride grafted POE; the lubricant is pentaerythritol stearate.

[0014] The preparation method of the above-mentioned recyclable glass fiber reinforced nylon / ABS alloy composite material comprises the following steps:

[0015] (1) Preparation of compatibilizer I: According to the weight fraction, weigh 64%-74% of nylon 6 resin, 24%-34% of ABS resin, and 1%-2% of lubricant. First, dry the nylon 6 resin and ABS resin at a drying temperature of 80-100°C and a drying time of 1-2 hours; mix the dried materials and lubricant in a high-speed mixer to obtain a mixed material; add the mixed material from the main feed port and convey it to the screw cavity of the twin-screw extruder, heat and melt at 220-245°C in the screw cavity, extrude and granulate, and sieve to obtain compatibilizer I;

[0016] (2) weighing raw materials according to weight percentage, including 25%-35% of low-carbon nylon material, 5%-15% of nylon resin, 6%-17% of glass fiber, 25%-30% of ABS resin, 0.2%-0.8% of primary antioxidant, 0.2%-0.8% of secondary antioxidant, 1%-5% of compatibilizer I, 1%-10% of compatibilizer II, 5%-13.5% of toughening agent and 1.5%-3% of nylon black masterbatch;

[0017] (3) The low-carbon nylon material, nylon resin and ABS resin are dried at 80-100°C for 4-6h; subsequently, the dried low-carbon nylon material, nylon resin, ABS resin, antioxidant, compatibilizer, toughening agent and black masterbatch are mixed in the high-speed mixer to obtain a mixture; then, the mixture is added from the main feed port and conveyed into the screw cavity of the twin-screw extruder, and the glass fiber is added from the side feed port and conveyed into the screw cavity of the twin-screw extruder, and the mixture is heated and melted at 220-240°C (the melting extrusion temperature of each section of the extruder is: 220°C-230°C for section 2-4, 230°C-240°C for section 5-8, 220°C-230°C for section 9-10, and 230°C for die head), extruded and granulated, and sieved to obtain a recyclable glass fiber reinforced nylon / ABS alloy composite material.

[0018] Specifically, the compatibilizer I in the present invention includes nylon 6 resin, ABS resin and lubricant. The compatibility of nylon 6 resin and ABS resin is relatively poor. The addition of lubricant can make the two resins more evenly dispersed. When the two resins are blended and melted, a small amount of resin will undergo chain exchange to form an interpenetrating network. In the formula, compatibilizer I is used as the main material on the one hand, and the compatible part does not need to consume the compatibilizer in the subsequent extrusion process. On the other hand, the chain exchange reaction occurs in the entire system. The chain exchange that has occurred will serve as a trigger factor to promote chain exchange in other parts to achieve the purpose of promoting compatibility. Compatibilizer II can introduce polar groups and increase the thickness of the interface layer. The polar groups can react with active groups to increase the adhesion between the two polymers and prevent the dispersed phase from condensing, making the dispersed phase and the continuous phase more uniform and stabilizing the formed phase morphology structure. In this way, incompatible polymers can be better mixed under intermolecular interactions to form a stable blend. Adding compatibilizer II can improve the processing performance and impact performance of the material. The main antioxidant can capture free radicals to delay thermal oxidation, and the auxiliary antioxidant can delay thermal oxidation by decomposing hydroperoxides. Therefore, the synergistic effect of the main antioxidant and the auxiliary antioxidant can effectively inhibit the thermal oxidation degradation of the composite material, improve the heat resistance of the composite material, and delay the degradation and aging process of the composite material, thereby extending the service life of the composite material. Maleic anhydride grafted POE as a toughening agent can effectively improve the impact performance of the material, and the polar groups it contains can make POE have better compatibility and adhesion with the material, and can also increase the surface tension of the material. The synergy of the compatibilizer and the toughening agent makes the surface tension of the material more uniform.

[0019] The above-mentioned recyclable glass fiber reinforced nylon / ABS alloy composite material is used in automobile production.

[0020] The beneficial effects produced by the present invention are:

[0021] (1) The present invention provides a recyclable glass fiber reinforced nylon / ABS alloy composite material, which reduces carbon emissions by recycling low-carbon nylon materials. Technically, only a small amount of glass fiber needs to be added to rebuild the skeleton structure of the repair material, thereby improving the strength and rigidity of the composite material. The easy-to-spray green low-carbon recyclable glass fiber reinforced nylon / ABS alloy composite material prepared by the formula ratio and preparation method of the present application improves the lightness and rigidity of the recycled material, further realizes the secondary utilization of the recycled material, and reduces the impact on the environment.

[0022] (2) The present invention can greatly improve the compatibility of the two resins through the synergistic effect between compatibilizer I and compatibilizer II. Specifically, in the formula, compatibilizer I is used as the main ingredient on the one hand, and the compatible part does not need to consume the compatibilizer in the subsequent extrusion process. On the other hand, the chain exchange reaction occurs in the entire system. The chain exchange that has occurred will serve as a trigger factor to promote the chain exchange of other parts, thereby achieving the purpose of promoting compatibility. Compatibilizer II can introduce polar groups and increase the thickness of the interface layer. The polar groups can react with the active groups to increase the adhesion between the two polymers and prevent the dispersed phase from agglomerating, making the dispersed phase and the continuous phase more uniform and stabilizing the formed phase morphology structure. In this way, incompatible polymers can be better mixed under intermolecular interactions to form a stable blend. At the same time, maleic anhydride grafted POE as a toughening agent can effectively improve the impact properties of the material, and the polar groups it contains can make POE have better compatibility and adhesion with the material, and can also increase the surface tension of the material. The synergy of compatibilizer and toughening agent makes the surface tension of the material more uniform, improves the adhesion of paint on the material surface, simplifies the complexity of the painting process, and meets the production needs of automobile OEMs. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 The present invention is a flow chart of a method for preparing a recyclable glass fiber reinforced nylon / ABS alloy composite material.

[0025] Figure 2 The figures are the actual pictures of the spraying of the present invention; wherein, (a) is the actual picture of the surface sprayed with paint; and (b) is the enlarged picture of the part. DETAILED DESCRIPTION

[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0028] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or obtained by existing methods.

[0029] The invention provides a recyclable glass fiber reinforced nylon / ABS alloy composite material, which comprises, by weight, 25%-35% of low-carbon nylon material, 5%-15% of nylon resin, 6%-17% of glass fiber, 25%-30% of ABS resin, 0.2%-0.8% of a primary antioxidant, 0.2%-0.8% of an auxiliary antioxidant, 1%-5% of a compatibilizer I, 1%-10% of a compatibilizer II, 5%-13.5% of a toughening agent and 1.5%-3% of a nylon black masterbatch.

[0030] The above-mentioned low-carbon nylon material is at least one of nylon 6 parts crushed material, nylon 6 head material, nylon 6 nozzle crushed material, nylon 6 black spot material, nylon 6 discolored material and nylon 6 mixed color material generated in the automobile production process; the nylon resin is nylon 6 resin. These nylon waste materials contain glass fiber and nylon resin. As long as a small amount of glass fiber is added, the skeleton structure of the material can be repaired, carbon emissions can be reduced, and production costs can be reduced; in addition, the addition of antioxidants can delay the thermal oxidation aging process of the composite material, thereby increasing the service life of the composite material; the addition of compatibilizers and toughening agents can improve the compatibility with the resin, enhance the mechanical properties of the composite material, and improve the adhesion between the resin and the paint. ABS resin also has the effect of improving the adhesion between the resin and the paint. The easy-to-spray green, low-carbon, recyclable glass fiber reinforced nylon / ABS alloy composite material prepared by the formula ratio and preparation method of the present invention can not only reuse the recycled materials, improve the material properties of the recycled materials, and reduce the impact on the environment, but also improve the adhesion of the paint on the material surface, simplify the complexity of the painting process, and meet the production needs of automobile main engine factories.

[0031] In some possible embodiments, the intrinsic viscosity of the nylon 6 resin is 2.45-2.8 dL / g.

[0032] Those skilled in the art will appreciate that the characteristic viscosity of nylon 6 resin is 2.45-2.8dL / g. Resin with this viscosity has a stronger ability to bind to glass fibers, and under high temperature, high speed and high pressure injection molding conditions, the glass fibers are not easily dispersed, have better dispersibility in the resin, and can achieve a better appearance.

[0033] In some possible embodiments, the glass fiber is short glass fiber that has been surface-treated with a coupling agent.

[0034] Those skilled in the art will understand that by selecting short glass fibers that have been surface-treated with a coupling agent, the coupling agent can change the wetting effect of the resin on the glass fiber surface and form a constraint layer to tightly bind the resin structure within the constraint layer, thereby improving the bonding ability between the resin and the glass fiber and improving the mechanical properties of the composite material.

[0035] In some possible embodiments, the antioxidant includes a primary antioxidant and a secondary antioxidant; wherein the primary antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; and the secondary antioxidant is tris[2,4-di-tert-butylphenyl]phosphite.

[0036] Since the primary antioxidant can capture free radicals and thus delay thermal oxidation, and the secondary antioxidant can delay thermal oxidation by decomposing hydroperoxides, the synergistic effect of the primary antioxidant and the secondary antioxidant can effectively inhibit the thermal oxidation aging degradation of the composite material, improve the heat resistance of the composite material, delay the degradation aging process of the composite material, and thus extend the service life of the composite material.

[0037] In some possible embodiments, the compatibilizer I is a self-made compatibilizer, and the compatibilizer II is ABS grafted with maleic anhydride or maleimide.

[0038] Specifically, compatibilizer I is a self-made compatibilizer, which consists of nylon 6 resin, ABS resin and lubricant. The compatibility of nylon 6 resin and ABS resin is relatively poor. The addition of lubricant can make the two resins more evenly dispersed. When the two resins are blended and melted, a small amount of resin will undergo chain exchange to form an interpenetrating network. On the one hand, the compatibilizer I is used as the main material in the formula, and the compatible part does not need to consume the compatibilizer in the subsequent extrusion process. On the other hand, the chain exchange reaction occurs in the entire system. The chain exchange that has occurred will serve as a trigger factor to promote chain exchange in other parts to achieve the purpose of promoting compatibility. Compatibilizer II can introduce polar groups and increase the thickness of the interface layer. The polar groups can react with the active groups to increase the adhesion between the two polymers and prevent the dispersed phase from condensing, making the dispersed phase and the continuous phase more uniform and stabilizing the formed phase morphology structure. In this way, incompatible polymers can be better mixed under intermolecular interactions to form a stable blend. Adding compatibilizer 2 can improve the processing performance and impact performance of the material.

[0039] In some possible embodiments, the ABS is produced by suspension polymerization and has a rubber content (butadiene content) of 20%-35% ABS resin.

[0040] Those skilled in the art can understand that ABS plastic is a terpolymer of acrylonitrile (A)-butadiene (B)-styrene (S). It combines the properties of three components, among which acrylonitrile has high hardness and strength, heat resistance and corrosion resistance; butadiene has impact resistance and toughness; styrene has high surface gloss, easy coloring and easy processing. The characteristics of the above three components make ABS plastic a thermoplastic plastic with good comprehensive properties of "hard, tough and rigid".

[0041] In some possible embodiments, the toughening agent is maleic anhydride grafted POE.

[0042] Those skilled in the art can understand that POE is a polyolefin elastomer and can be used as a toughening agent. Toughening agents are a type of additive that can reduce the brittleness of composite materials and improve the impact resistance of composite materials. Adding toughening agents can effectively improve the impact resistance of materials. Maleic anhydride brings polar groups to POE, which can make POE have better compatibility and adhesion with materials.

[0043] Experimental materials:

[0044] Low carbon nylon material: nylon 6 mixed color scraps

[0045] Nylon 6 resin: Yuehua YH800

[0046] Fiberglass: Jushi Group 568HD

[0047] ABS resin: Chimei PA-757K

[0048] Main antioxidant: pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, Lionon antioxidant 1010

[0049] Auxiliary antioxidants: tris[2,4-di-tert-butylphenyl]phosphite, Lionon antioxidant 168

[0050] Compatibilizer I: Homemade compatibilizer

[0051] Compatibilizer II: ABS grafted with maleic anhydride, Starbeida ST-4210

[0052] Toughening agent: Maleic anhydride grafted POE, Coase W1A

[0053] Nylon black masterbatch: Cabot PA3785

[0054] The effects of different compatibilizer components on the properties of composite materials were investigated separately, as shown below:

[0055] Compatibilizer I Preparation Example 1

[0056] According to the weight fraction, 64% nylon 6 resin, 34% ABS resin and 2% lubricant pentaerythritol stearate are weighed. First, the nylon 6 resin and ABS resin are dried at 80°C for 2 hours; the dried materials and lubricant are mixed in a high-speed mixer to obtain a mixed material; the mixed material is added from the main feed port and conveyed to the screw cavity of the twin-screw extruder, heated and melted at 220-245°C in the screw cavity, extruded and granulated, and sieved to obtain compatibilizer I.

[0057] Compatibilizer I Preparation Example 2

[0058] According to the weight fraction, 69% of nylon 6 resin, 30% of ABS resin and 1% of lubricant pentaerythritol stearate are weighed. First, the nylon 6 resin and ABS resin are dried at 90°C for 2 hours; the dried materials and lubricant are mixed in a high-speed mixer to obtain a mixed material; the mixed material is added from the main feed port and conveyed to the screw cavity of the twin-screw extruder, heated and melted at 220-245°C in the screw cavity, extruded into granules, and sieved to obtain compatibilizer I.

[0059] Compatibilizer I Preparation Example 3

[0060] According to the weight fraction, 74% of nylon 6 resin, 24% of ABS resin and 2% of lubricant pentaerythritol stearate are weighed. First, the nylon 6 resin and ABS resin are dried at a drying temperature of 100°C and a drying time of 1 hour; the dried materials and the lubricant are mixed in a high-speed mixer to obtain a mixed material; the mixed material is added from the main feed port and conveyed to the screw cavity of the twin-screw extruder, heated and melted at 220-245°C in the screw cavity, extruded into granules, and sieved to obtain compatibilizer I.

[0061] The mechanical properties of the compatibilizer I prepared in Preparation Examples 1-3 were tested, and the performance results are shown in Table 1. The specific test standards are as follows:

[0062] Tensile performance test: the test standard is ISO 527, the tensile rate is 50mm / min.

[0063] Bending performance test: Test standard ISO-178, bending rate is 2mm / min.

[0064] Charpy notched impact strength: test standard ISO-179.

[0065] Table 1 Performance results

[0066] Performance Testing Preparation Example 1 Preparation Example 2 Preparation Example 3 Tensile strength(MPa) 24 23 20 Bending strength(MPa) 35 32 31 <![CDATA[Notched impact strength of simply supported beam (KJ / m 2 )]]> 2.9 3.1 3.2

[0067] From the above performance comparison in Table 1, it can be seen that the compatibilizer I prepared within the formula range of 64%-74% of nylon 6 resin, 24%-34% of ABS resin, and 1%-2% of lubricant pentaerythritol stearate has little difference in performance. Generally speaking, the better the compatibility, the better the performance of the material. Therefore, the compatibility of the compatibilizer I within this formula range is not much different. When preparing the composite material later, the formula of Preparation Example 2 is selected as the compatibilizer I.

[0068] Example 1

[0069] The preparation method of the recyclable glass fiber reinforced nylon / ABS alloy composite material of this embodiment is as follows: Figure 1 The steps are as follows:

[0070] (1) Weighing raw materials according to weight percentage, including 25% of low-carbon nylon material, 15% of nylon 6 resin, 17% of glass fiber, 25% of ABS resin, 0.2% of primary antioxidant, 0.8% of secondary antioxidant, 1% of compatibilizer I, 1% of compatibilizer II, 13.5% of toughening agent and 1.5% of nylon black masterbatch;

[0071] (2) The low-carbon nylon material, nylon resin and ABS resin are dried at 80°C for 6h; subsequently, the dried low-carbon nylon material, nylon resin, ABS resin, antioxidant, compatibilizer, toughening agent and black masterbatch are mixed in the high-speed mixer to obtain a mixture; then, the mixture is added from the main feed port and conveyed into the screw cavity of the twin-screw extruder, and the glass fiber is added from the side feed port and conveyed into the screw cavity of the twin-screw extruder, and the temperature of each section is set as follows: 220°C for section 2, 220°C for section 3, 220°C for section 4, 230°C for section 5, 230°C for section 6, 230°C for section 7, 230°C for section 8, 220°C for section 9, 220°C for section 10 and 230°C for die head; and a recyclable glass fiber reinforced nylon / ABS alloy composite material is obtained by heating and melting, extruding granulation and screening.

[0072] Example 2

[0073] The preparation method of the recyclable glass fiber reinforced nylon / ABS alloy composite material of this embodiment comprises the following steps:

[0074] (1) Weighing raw materials according to weight percentage, including 30% low-carbon nylon material, 10% nylon 6 resin, 12% glass fiber, 27% ABS resin, 0.5% primary antioxidant, 0.5% secondary antioxidant, 3% compatibilizer I, 6% compatibilizer II, 9% toughening agent and 2% nylon black masterbatch;

[0075] (2) The low-carbon nylon material, nylon resin and ABS resin are dried at 90° C. for 5 h; subsequently, the dried low-carbon nylon material, nylon resin, ABS resin, antioxidant, compatibilizer, toughening agent and black masterbatch are mixed in the high-speed mixer to obtain a mixture; then, the mixture is added from the main feed port and conveyed into the screw cavity of the twin-screw extruder, and the glass fiber is added from the side feed port and conveyed into the screw cavity of the twin-screw extruder, and the temperature of each section is set as follows: 230° C. for section 2, 230° C. for section 3, 230° C. for section 4, 240° C. for section 5, 240° C. for section 6, 240° C. for section 7, 240° C. for section 8, 230° C. for section 9, 230° C. for section 10 and 240° C. for die head; and a recyclable glass fiber reinforced nylon / ABS alloy composite material is obtained by heating, melting, extruding, granulating and screening.

[0076] Example 3

[0077] The preparation method of the recyclable glass fiber reinforced nylon / ABS alloy composite material of this embodiment comprises the following steps:

[0078] (1) Weighing raw materials according to weight percentage, including 35% of low-carbon nylon material, 5% of nylon 6 resin, 6% of glass fiber, 30% of ABS resin, 0.8% of primary antioxidant, 0.2% of secondary antioxidant, 5% of compatibilizer I, 10% of compatibilizer II, 5% of toughening agent and 3% of nylon black masterbatch;

[0079] (2) The low-carbon nylon material, nylon resin and ABS resin are dried at 100° C. for 4 h; subsequently, the dried low-carbon nylon material, nylon resin, ABS resin, antioxidant, compatibilizer, toughening agent and black masterbatch are mixed in the high-speed mixer to obtain a mixture; then, the mixture is added from the main feed port and conveyed into the screw cavity of the twin-screw extruder, and the glass fiber is added from the side feed port and conveyed into the screw cavity of the twin-screw extruder, and the temperature of each section is set as follows: 225° C. for section 2, 225° C. for section 3, 225° C. for section 4, 235° C. for section 5, 235° C. for section 6, 235° C. for section 7, 235° C. for section 8, 225° C. for section 9, 225° C. for section 10, and 235° C. for the die; and a recyclable glass fiber reinforced nylon / ABS alloy composite material is obtained by heating and melting, extruding granulation and screening.

[0080] Comparative Example 1

[0081] The preparation method of the recyclable glass fiber reinforced nylon / ABS alloy composite material of this comparative example comprises the following steps:

[0082] The raw materials are weighed according to weight percentage, including 30% of low-carbon nylon material, 12% of nylon 6 resin, 13% of glass fiber, 27% of ABS resin, 0.5% of primary antioxidant, 0.5% of secondary antioxidant, 6% of compatibilizer II, 9% of toughening agent and 2% of nylon black masterbatch;

[0083] The preparation process is the same as that of Example 2.

[0084] Comparative Example 2

[0085] The preparation method of the recyclable glass fiber reinforced nylon / ABS alloy composite material of this comparative example comprises the following steps:

[0086] The raw materials are weighed according to weight percentage, including 30% of low-carbon nylon material, 12% of nylon 6 resin, 13% of glass fiber, 27% of ABS resin, 0.5% of primary antioxidant, 0.5% of secondary antioxidant, 6% of compatibilizer I, 9% of toughening agent and 2% of nylon black masterbatch;

[0087] The preparation process is the same as that of Example 2.

[0088] Comparative Example 3

[0089] The preparation method of the recyclable glass fiber reinforced nylon / ABS alloy composite material of this comparative example comprises the following steps:

[0090] The raw materials are weighed according to weight percentage, including 30% of low-carbon nylon material, 15% of nylon 6 resin, 15% of glass fiber, 28% of ABS resin, 0.5% of primary antioxidant, 0.5% of secondary antioxidant, 3% of compatibilizer I, 6% of compatibilizer II and 2% of nylon black masterbatch;

[0091] The preparation process is the same as that of Example 2.

[0092] Comparative Example 4

[0093] The preparation method of the recyclable glass fiber reinforced nylon / ABS alloy composite material of this comparative example comprises the following steps:

[0094] The raw materials are weighed according to weight percentage, including 58% of low-carbon nylon material, 15% of nylon 6 resin, 15% of glass fiber, 0.5% of primary antioxidant, 0.5% of secondary antioxidant, 9% of toughening agent and 2% of nylon black masterbatch;

[0095] The preparation process is the same as that of Example 2.

[0096] The specific formulas of Examples 1-3 and Comparative Examples 1-4 are shown in Table 2:

[0097] Table 2 Recipe

[0098] Component / wt% Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Nylon 6 mixed color scraps 25 30 35 30 30 30 58 ABS resin 25 27 30 27 27 28 - Nylon 6 resin 15 10 5 12 12 15 15 Fiberglass 17 12 6 13 13 15 15 Primary Antioxidant 0.2 0.5 0.8 0.5 0.5 0.5 0.5 Secondary antioxidant 0.8 0.5 0.2 0.5 0.5 0.5 0.5 Compatibilizer Ⅰ 1 3 5 - 6 3 - Compatibilizer Ⅱ 1 6 10 6 - 6 - Toughening agent 13.5 9 5 9 9 - 9 Black mother 1.5 2 3 2 2 2 2

[0099] Implementation effect example

[0100] In the actual production process, some waste materials will inevitably be generated due to the process, such as broken parts, black spot materials, unqualified products generated in the production process of automobile parts, or some head materials and broken gate materials generated in the injection molding process. If the above waste materials are simply disposed of, it is undoubtedly a huge waste of resources. If these waste materials can be recycled and reused, it will play a huge role in reducing costs, increasing efficiency, energy saving and environmental protection. Embodiments 1-3 of the present invention and comparative examples 1-4 use nylon 6 variegated scraps in this type of waste as low-carbon nylon materials. Although these recycled low-carbon nylon materials themselves still have a certain strength, they cannot meet the requirements of the product, so it is necessary to add glass fiber and nylon 6 resin to improve the strength of the composite material, and at the same time, use ABS resin, compatibilizer, toughening agent, black masterbatch and nylon resin to react, thereby improving the compatibility of the raw materials between the materials, and then improving the mechanical properties, stability and adhesion of the composite material to the external paint.

[0101] The performance of the recyclable glass fiber reinforced nylon / ABS alloy composite material prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention was tested, and the test method is as follows:

[0102] Spraying effect test and deformation test: Spray according to the spraying process of plastic parts. Observe the spraying effect and deformation effect after spraying. The spraying process mainly includes: solvent cleaning → water drying → electrostatic dust removal → paint spraying → paint drying.

[0103] Peeling test: Put the sprayed plastic parts into a high and low temperature test chamber, set the test temperature to 100℃, the test humidity to 80%, take them out after 90 days, and observe the paint shedding.

[0104] The following tests are performance tests after spraying.

[0105] Tensile performance test: the test standard is ISO 527, the tensile rate is 50mm / min.

[0106] Bending performance test: Test standard ISO-178, bending rate is 2mm / min.

[0107] Charpy notched impact strength: test standard ISO-179.

[0108] The test results of the above performance are shown in Table 3.

[0109] Table 3 Test results

[0110]

[0111] Comparing the test results in Table 3 above, it can be found by comparing Examples 1-3 that the amount of recycled material added has a certain influence on the performance of the material. The more recycled material is added, the worse the performance of the material is. This is because the integrity of the glass fiber inside the recycled material is damaged to a certain extent during the secondary extrusion, and the recycled material will be physically destroyed during multiple heating and processing, resulting in polymer degradation. Therefore, it can be seen that recycled materials cannot be used directly without modification. The actual picture of the surface sprayed with paint in Example 2 is as follows: Figure 2 As shown in the figure, it can be seen that there are no defects on the sprayed surface of the sample, the surface is smooth and flat, and the sample has no deformation or paint falling off.

[0112] By comparing Example 2 with Comparative Examples 1-4, it can be seen that when the self-made compatibilizer I is added, the compatibility of nylon 6 resin and ABS resin can be better improved. Without the addition of the self-made compatibilizer I, most of the performance can meet the use requirements. However, due to the slightly poor compatibility, the surface tension of some areas on the surface of the material is insufficient. Although the paint does not sag after spraying, it will fall off after high temperature and high humidity testing. However, in Comparative Example 2, although the self-made compatibilizer I can play a certain ability to promote compatibility, it cannot replace the real compatibilizer. The self-made compatibilizer I can promote chain exchange. Compared with the introduction of polar groups of the compatibilizer, the process is slow and cannot promote the overall chain exchange. Therefore, the synergistic effect of compatibilizer I and compatibilizer II can greatly improve the compatibility of the two resins, and the performance is also greatly improved. The toughening agent will bring about a significant increase in impact strength, and can also increase the surface tension of the material. The synergy of the compatibilizer and the toughening agent makes the surface tension of the material more uniform. In summary, the addition amount of low-carbon nylon material ≥ 20wt% can meet the GRS requirements.

[0113] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A recyclable glass fiber reinforced nylon / ABS alloy composite material, characterized in that: By weight, it includes 25%-35% of low-carbon nylon material, 5%-15% of nylon resin, 6%-17% of glass fiber, 25%-30% of ABS resin, 0.2%-0.8% of primary antioxidant, 0.2%-0.8% of secondary antioxidant, 1%-5% of compatibilizer I, 1%-10% of compatibilizer II, 5%-13.5% of toughening agent and 1.5%-3% of nylon black masterbatch; Wherein, compatibilizer I includes nylon 6 resin 64%-74%, ABS resin 24%-34% and lubricant 1%-2%.

2. The recyclable glass fiber reinforced nylon / ABS alloy composite material according to claim 1, characterized in that: The low-carbon nylon material is at least one of nylon 6 parts crushed material, nylon 6 head material, nylon 6 nozzle crushed material, nylon 6 black spot material, nylon 6 discolored material and nylon 6 mixed color material generated in the automobile production process.

3. The recyclable glass fiber reinforced nylon / ABS alloy composite material according to claim 2, characterized in that: The nylon resin is nylon 6 resin with an intrinsic viscosity of 2.45-2.8 dL / g; the ABS resin is prepared by suspension polymerization and has a rubber content of 20-35%.

4. The recyclable glass fiber reinforced nylon / ABS alloy composite material according to claim 3, characterized in that: The glass fiber is short glass fiber surface-treated with a coupling agent.

5. The recyclable glass fiber reinforced nylon / ABS alloy composite material according to claim 4, characterized in that: The main antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], and the auxiliary antioxidant is tris[2,4-di-tert-butylphenyl]phosphite.

6. The recyclable glass fiber reinforced nylon / ABS alloy composite material according to claim 5, characterized in that: The compatibilizer II is ABS grafted with maleic anhydride or maleimide.

7. The recyclable glass fiber reinforced nylon / ABS alloy composite material according to claim 6, characterized in that: The toughening agent is maleic anhydride grafted POE; the lubricant is pentaerythritol stearate.

8. The method for preparing the recyclable glass fiber reinforced nylon / ABS alloy composite material according to claims 1-7, characterized in that: Here are the steps: (1) Mixing the dried nylon 6 resin and ABS resin with a lubricant, and melt-extruding and granulating them to obtain compatibilizer I; (2) The dried low-carbon nylon material, nylon resin and ABS resin are mixed with glass fiber, primary antioxidant, secondary antioxidant, compatibilizer I, compatibilizer II, toughening agent and nylon black masterbatch, and the mixture is melt-extruded, granulated and sieved to obtain a recyclable glass fiber reinforced nylon / ABS alloy composite material.

9. The method for preparing the recyclable glass fiber reinforced nylon / ABS alloy composite material according to claim 8, characterized in that: The temperature of each section of the melt extrusion is: 220°C-230°C for sections 2-4, 230°C-240°C for sections 5-8, 220°C-230°C for sections 9-10, and 230°C-240°C for the die.

10. Use of the recyclable glass fiber reinforced nylon / ABS alloy composite material according to claim 1 in automobile production.

Citation Information

Patent Citations

  • PA (polyamide) / ABS (acrylonitrile-butadiene-styrene copolymer) alloy material and preparation method thereof

    CN105504654A